Changes in soil enzymes, soil properties, and maize crop productivity under wheat straw mulching in Guanzhong, China - Akhtar, Kashif; Wang, Weiyu; Ren, Guangxin; Khan, Ahmad; Feng, Yongzhong; Yang, Gaihe (Soil & tillage research, 2018)
•Straw mulch was effective in increasing soil organic carbon (SOC) content.•Straw mulch improves the soil N, P and soil water content in 0–10 cm soil layer.•Straw mulch treatments significantly increased the soil enzyme activity.•Enzyme activities are related to nutrient dynamics, particularly SOC and available N.•The crop yield and water use efficiency were significantly higher with straw mulch. Addition of organic material, such as crop straw mulch in most soils is considered a strategy for sustainable agricultural production. We conducted a two-year experiment in 2015 and 2016 to determine changes in soil biochemical properties and maize yield in response to treatment with wheat-straw mulch. The treatments consisted of the addition of different levels of wheat-straw mulch (S1: 0, S2: 2500, S3: 5000 kg ha−1). Soil samples from four depths (0.1, 0.2, 0.3, and 0.4 m) were collected and analyzed. Soil enzymes, such as invertase, phosphatase, urease, and catalase, were significantly higher in the S3 treatment than in the S1 treatment. Values were greater for the samples collected at 0.1 m soil depth than those collected from deeper soil layers. Regarding soil properties, soil organic carbon (SOC), available nitrogen (AN), available phosphorus (AP), total nitrogen (TN), total phosphorus (TP), and soil water content (SWC) were significantly higher in S3 at 0–0.1 m soil depth than in other treatments. Compared with the (S1), an average increase in SOC, AN, AP, TN, TP, and SWC in 0–0.4 m soil depth with full straw mulch (S3), were 32.4, 31.9, 32.0, 11.8, 16.7, and 18.5%, higher, respectively. On average, urease, phosphatase, invertase, and catalase increased by 15.1, 11.0, 88.4, and 24.0%, respectively in the S3 treatment compared with that in the S1 treatment at 0–0.1 m depth, and decreased with increasing soil depth. The S3 treatment had increased grain yield (7%), biomass yield (28%), and water use efficiency (8%), compared with the S1 treatment. Overall, our results suggested that the S3 straw mulch treatment (5000 kg ha−1) could be used to sustain maize productivity and promote a better relationship between soil enzymes and soil properties in the semi-arid conditions of the Guanzhong area.